Can't fail room makeovers /c Lucianna Samu ; photography by Mark Samu - Samu, Lucianna (Creative Homeowner, 2008)
This book contains everything someone needs to know to show off a home to its fullest potential with easy ideas and advice for making rooms work. The book includes how to "edit" the decor, rearrange furniture, display artwork and collections, transform rooms and objects with paint, and much more